SUDANESE PHARMACY STUDENTS: CAREER INTENTIONS, EXPECTATIONS AND FACTORS AFFECTING THEIR CHOICES - Alhemadey, Hebatallah; Mousnad, Mohamed Awad; Saeed, Ali Awadallah; Hamid, Azza (Universal Journal of Pharmaceutical Research, 2021)
Objectives: Pharmacy is a profession with wide careers. The desires to study pharmacy affect selection of pharmacy careers. Despite that in the last years pharmacy careers had developed and expanded , majority of the pharmacists end up in hospital or community pharmacy that create imbalance in distribution of pharmacists and shortage in work force. This may be due to career pathways were not clearly addressed as part of the pharmacy curriculum. Objective of present study was to assess final year pharmacy student’s career intentions, expectations and factors affecting their choices in Khartoum state. Material and Methods: This study is an observational cross-sectional, study conducted during the period of time from September 2017 to April 2018 for 257 final year pharmacy students selected by non-random convenient sampling in the four universities, data analyzed using SPSS version 21. Results: There were wide factors can affect students to study pharmacy; family was the most effective factor (46.7%) and the desire to work in medical profession (44.4%). Approximately 53% of the students are satisfied with studying pharmacy. The level of satisfaction was significantly associated with gender and whether pharmacy was their first choice. (P value =0.001). There was significant different in response of career intention regarding attendance in career advice sessions (P =0.035). Student's opinions about each career were as follows: community pharmacy as the most familiar (69.3%), academia as the most prestigious (31.1%), clinical pharmacy as the most stressful (32.3%), marketing and industrial pharmacy as the ones with highest salary (59.5% and 22.2%) and regulatory affairs as the most unfamiliar career (69.6%). There was significant different between career intention and salary (P value =0.00). Conclusion: The most intended careers were hospital and marketing. Personal desire, chances for development, working environment and salary were the most factors affecting student's career intention. Career advice program should be incorporated into the curriculum. Peer Review History: Received 4 October 2020; Revised 12 November; Accepted 20 December; Available online 15 January 2021 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewer(s) detail: Dr. Evren Alğin Yapar , Turkish Medicines and Medical Devices Agency, Turkiye, evren.yapar@yahoo.com Dr. Muhammad Zahid Iqbal , AIMST University, Malaysia, drmmziqbal@gmail.com